2020
DOI: 10.1111/eci.13239
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability underlying disability amongst older adults: A systematic review

Abstract: Background: Older adults face radical changes in their social life during ageing, dealing with several age-related social adaptations. The aim of this review is to systematically explore the literature on social vulnerability (SV) and its association with functional decline activity of daily living (ADL)/instrumental activities of daily living (IADL) as an endpoint in older adults. Methods: We searched for relevant studies in three different databases: PubMed, Ovid Medline and PsychInfo. Inclusion criteria inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
(308 reference statements)
1
8
0
1
Order By: Relevance
“…The potential cohort effect may explain the higher SVI values noted in Taiwan compared with other Western countries. The dose-responsive effects between SVI and depressive symptoms, cognitive impairment, physical dependency, and multimorbidity were identified in this study, and these results were similar to those noted in previous studies [ 10 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…The potential cohort effect may explain the higher SVI values noted in Taiwan compared with other Western countries. The dose-responsive effects between SVI and depressive symptoms, cognitive impairment, physical dependency, and multimorbidity were identified in this study, and these results were similar to those noted in previous studies [ 10 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, this potential in wealthy and higher social groups is challenged by the lack of specific public interventions of proven effectiveness and efficacy in socioeconomically poor frail individuals [ 42 ]. This may be substantiated by studies on the association of lack of social resources among the poor people with their functional decline in old age [ 43 ]. The previous findings in India suggesting that rural populations are disproportionately affected by poor health outcomes due to barriers to diagnosis also suggest their increased vulnerability to physical frailty in old age [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities and frailty, that arise with increasing age [ 11 ], are linked with rising risks of the onset of ill health and disability [ 5 , 8 , 12 ]. Studies showed that in general, older age, being women, lower education, lower economic status and not living with a partner are social adversity factors that were associated with worse health and quality of life [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%